Design, Synthesis and X‐Ray Structural Studies of Potent HIV‐1 Protease Inhibitors Containing C‐4 Substituted Tricyclic Hexahydro‐Furofuran Derivatives as P2 Ligands. (4th March 2022) - Ghosh, Arun K.; Kovela, Satish; Sharma, Ashish; Shahabi, Dana; Ghosh, Ajay K.; Hopkins, Denver R.; Yadav, Monika; Johnson, Megan E.; Agniswamy, Johnson; Wang, Yuan‐Fang; Hattori, Shin‐Ichiro; Higashi‐Kuwata, Nobuyo; et al.
Abstract: The design, synthesis, X‐ray structural, and biological evaluation of a series of highly potent HIV‐1 protease inhibitors are reported herein. These inhibitors incorporate novel cyclohexane‐fused tricyclic bis ‐tetrahydrofuran as P2 ligands in combination with a variety of P1 and P2′ ligands. The inhibitor with a difluoromethylphenyl P1 ligand and a cyclopropylaminobenzothiazole P2′ ligand exhibited the most potent antiviral activity. Also, it maintained potent antiviral activity against a panel of highly multidrug‐resistant HIV‐1 variants. The corresponding inhibitor with an enantiomeric ligand was significantly less potent in these antiviral assays. The new P2 ligands were synthesized in optically active form using enzymatic desymmetrization of meso ‐diols as the key step. To obtain molecular insight, two high‐resolution X‐ray structures of inhibitor‐bound HIV‐1 protease were determined and structural analyses have been highlighted. Abstract : Molecular insight : Herein we report the design, synthesis, biological evaluation, and X‐ray structural studies of a series of potent HIV‐1 protease inhibitors containing a cyclohexane‐fused tricyclic bis ‐tetrahydrofuran‐based P2 ligands to interact with active site residues in the S2‐subsite.